Characteristics of short-patent auditory evoked potentials in children with cerebral palsy - V. V. Dulnev; Т. A. Slyusar’ (Нервно-мышечные болезни, 2019)
Background. In children with cerebral palsy, high risk of cognitive impairments connected with sensory disintegration – delayed visual and auditory perception.The objective – assessment of temporary and amplitude characteristics brainstem auditory evoked potentials of children with cerebral palsy.Materials and methods. Neurological examination, retrospective analysis of magnetic resonance imaging data of brain and 2-channel brainstem auditory evoked potentials registration with left- and right-ear stimulation and analysis was performed for 60 children aged 4–17 years, with mean age 11.80 ± 0.56 years.Results. There are no significant difference in brainstem auditory evoked potentials latencies of children’s with cerebral palsy age subgroups. A significantly increasing of III–V peak latencies of brainstem auditory evoked potentials and also I–III and I–V interpeak latencies was observed in children with cerebral palsy in comparison of control group. Latencies of different brainstem auditory evoked potentials peaks were significantly higher in children with uni- and bilateral form of cerebral palsy and speech impairment. Group with periventricular leucomalation (on magnetic resonance imaging) is characterized by significantly increased brainstem auditory evoked potentials latencies and normal interpeak intervals. These abnormalities may be linked to non-progressive impairment of brainstem acoustic afferentation.Conclusion. Impairment of brainstem auditory evoked potentials maturation and it’s difference in various cerebral palsy forms may be potentially clinical applicable for assessment of the children and early detection of sensory impairment.